Refractive results of cataract surgery using optical biometry and Haigis formula in eyes with refractive keratotomy - Juan Carlos Sánchez Caballero; Virgilio Centurion (Revista Brasileira de Oftalmologia, 2013)
OBJECTIVE: To analyze refractive results in postoperative cataract surgery in eyes previously submitted to keratotomy using Haigis formula and data provided by IOL Master®optical biometer. METHODS: The measurements for IOL calculation were obtained through optical biometry by partial coherence interferometry (IOL Master®- Zeiss, 5.4 and 5.5 version) that provides us with the axial length, the central keratometry of 2.5mm, white-to-white diameter and anterior chamber anatomical depth. The formula chosen was Haigis. The surgical technique applied was with the scleral incision at 1.5 mm from the limbus, with scleral-corneal tunnel of 2.2 mm wide, phacoemulsification using INFINITI Ozil®- Alcon and implantation of hydrophobic acrylic aspheric intraocular lens - SN60WF®- Alcon. RESULTS: We studied 20 eyes submitted to keratotomy in the past and currently with cataract with indication for cataract surgerywith intraocular lens implantation using phacoemulsification. Postoperative spherical equivalent was plano in 40% of the eyes and lower than -1.00 in 85% of the eyes. CONCLUSION: The optical biometry by partial coherence interferometry associated with Haigis formula is a valid alternative in IOL calculation for eyes submitted to keratotomy. The refractive results are highly predictable and reproducible.